An exchange coupled meso–meso linked vanadyl porphyrin dimer for quantum information processing. Issue 1 (21st November 2022) - Ranieri, Davide; Santanni, Fabio; Privitera, Alberto; Albino, Andrea; Salvadori, Enrico; Chiesa, Mario; Totti, Federico; Sorace, Lorenzo; Sessoli, Roberta
Abstract : A combined EPR and DFT study of a suitably designed vanadyl-porphyrin dimer revealed promising properties for quantum information processing applications, such as single qubit addressability and relevant intramolecular exchange interactions. Abstract : We report here the synthesis of a new meso – meso ( m – m ) singly linked vanadyl–porphyrin dimer that crystallizes in two different pseudo-polymorphs. The single crystal continuous-wave electron paramagnetic resonance investigation evidences a small but crucial isotropic exchange interaction, J, between the two tilted, and thus distinguishable, spin centers of the order of 10 −2 cm −1 . The experimental and DFT studies evidence a correlation between J values and porphyrin plane tilting angle and distortion. Pulsed EPR analysis shows that the two vanadyl dimers maintain the coherence time of the monomer. With the obtained spin Hamiltonian parameters, we identify suitable transitions that could be used as computational basis states. Our results, coupled with the evaporability of porphyrin systems, establish this class of dimers as extremely promising for quantum information processing applications.